Does Economic Growth Raise Happiness in China? A Comprehensive Reexamination. Issue 2 (March 2023) - Cai, Huajian; Yuan, Jingqi; Su, Zhan; Wang, Xiaoou; Huang, Zihang; Jing, Yiming; Yang, Ziyan
Has China's vigorous economic growth raised its citizens' happiness? Existing studies have portrayed, if not a pessimistic picture, a complicated one. We conducted two studies to clarify this issue. In Study 1, we used data from available national surveys between 1990 and 2018 (64 samples) and demonstrated a significant quadratic U-shaped trend and a rising tendency. In Study 2, we conducted a cross-temporal meta-analysis from 2001 to 2019 (689 samples) and found that Chinese happiness manifested a linear rising trend, although this trend was more salient in the community sample than in the student one. In both studies, Granger causal analysis suggested that economic growth was the Granger cause of the increase in Chinese happiness. These findings indicate that economic growth has raised happiness in China since 1990, particularly since 2001, and highlight the importance of moving beyond the Easterlin Paradox.